When divided by x − 1 the polynomial p ( x ) leaves a remainder 2 .When divided by x − 2 leaves a remainder 5.When divided by ( x − 1 ) ( x − 2 ) leaves a remainder of the form a x + b . Evaluate a .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
awesome...
I solve it the same way as you did...
From the question , we have:
x
−
1
p
(
x
)
=
f
(
x
)
+
x
−
1
2
(
1
)
x
−
2
p
(
x
)
=
h
(
x
)
+
x
−
2
5
(
2
)
Substracting
(
1
)
from
(
2
)
,we obtain:
(
x
−
1
)
(
x
−
2
)
p
(
x
)
=
h
(
x
)
−
f
(
x
)
+
(
x
−
1
)
(
x
−
2
)
3
x
−
1
p
(
x
)
=
(
h
(
x
)
−
f
(
x
)
)
(
x
−
1
)
(
x
−
2
)
+
3
x
−
1
,therefore the remainder is
3
x
−
1
, where we obtain
a
=
3
Respectively, let q ( x ) , r ( x ) and s ( x ) be the quotient when p ( x ) is divided by ( x − 1 ) , ( x − 2 ) , and ( x − 1 ) ( x − 2 ) . Hence we can rewrite p ( x ) as below:
p ( x ) = ( x − 1 ) q ( x ) + 2 . . . ( 1 )
p ( x ) = ( x − 2 ) r ( x ) + 5 . . . ( 2 )
p ( x ) = ( x − 1 ) ( x − 2 ) s ( x ) + a x + b . . . ( 3 )
From (1) we have p ( 1 ) = ( 1 − 1 ) q ( x ) + 2 = 0 + 2 = 2
Similarly, from (2) we have p ( 2 ) = 5
Thus p ( 1 ) = p ( 2 ) . But from (3) we have p ( 1 ) = p ( 2 ) = a x + b
Indirectly, it is stated that p ( 1 ) = p ( 2 ) and p ( 1 ) = p ( 2 ) at once
This is impossible unless q ( x ) = r ( x ) = s ( x ) = 0 , such that it results the new conclution: p ( x ) = a x + b .
Therefore, now we have p ( 1 ) = a + b = 2 and p ( 2 ) = 2 a + b = 5 . And p ( 2 ) − p ( 1 ) = a = 3
p(x) = (x-1)(x-2) f(x) + (ax+b) where f(x) is quotient and ax+b is the remainder. On applying the first two conditions, i.e., when x=1 p(x)=2 and x=2 p(x)=5; a+b = 2 and 2a+b=5. Solving the above two equations, we get a=3 and b=-1
2 = a + b , 5 = 2a + b, So, with substitution method we have b = -1 and a = 3. Answer : 3
You should elaborate on your solution.
From the given statement, we can express that
P(x) = (x-1) Q(x) + 2 => P(1) = 2 P(x) = (x-2) K(x) + 5 => P(2) = 5
Finally: P(x) = (x-1)(x-2) H(x) + ax + b Replace x by 1 and 2, we have a + b = 2 2a + b = 5 => a = 3
Can admin fix my post :( It's hard to read :(
It follows easily from Chinese Remainder Theorem .We get: a x + b = 3 x − 2 giving a = 3 .
Can you please explain that what is chinese remainder theoram??
Log in to reply
The Chinese Remainder Theorem has nearly nothing to do with the algebra of polynomials, as far as I know. It's a result about modular congruences in number theory.
Log in to reply
This is true. However, we can easily generalize the CRT to any commutative ring. The method would not be as easy as Bhargav claims, unless Bhargav is using something clever that he's not saying, but it would get you p ( x ) by using a fairly simple algorithm.
Yes, historically this was a theorem about the integers. However, almost everything that works for numbers, works for polynomials, including, as Jacob Erickson noted, the Chinese Remainder Theorem. My favorite example of this kind is the construction of complex numbers as real polynomials modulo the irreducible polynomial x 2 + 1 .
It does not quite work the other way. For example, the arithmetic analog of the Mason-Stothers theorem is the notoriously hard abc-conjecture.
I actually became a bit of a lethargic that day.So,let me clear things up now. Here goes:
STEP 1 : A/Q we have, p ( x ) ≡ 2 ( m o d ( x − 1 ) )
and p ( x ) ≡ 5 ( m o d ( x − 2 ) )
Let b 1 and b 2 be 2 and 5 respectively.
We need to find: p ( x ) ≡ ∗ ( m o d ( x − 1 ) ( x − 2 ) ) ,where ∗ is of the form a x + b and where a and b are integers.
STEP 2 : Let M = ( x − 1 ) ( x − 2 ) .
Hence, M 1 = x − 1 M = ( x − 2 ) and M 2 = x − 2 M = ( x − 1 ) .
STEP 3 : We need to find x 1 in: M 1 x 1 ≡ 1 ( m o d ( x − 1 ) ) .
⟹ x 1 = − 1 (Self-explanatory).
Similarly, We need to find x 2 in: M 2 x 2 ≡ 1 ( m o d ( x − 1 ) ) .
⟹ x 2 = 1 (Self-explanatory).
STEP 4 : X = b 1 M 1 x 1 + b 2 M 2 x 2 + b 3 M 3 x 3 = 2 ⋅ ( x − 2 ) ⋅ ( − 1 ) + 5 ⋅ ( x − 1 ) ⋅ 1 = 3 x − 1
X = b 1 M 1 x 1 + b 2 M 2 x 2 + b 3 M 3 x 3 = 3 x − 1 ≡ ( 3 x − 1 ) ( m o d ( x − 1 ) ( x − 2 ) ) .
Hence, ⟹ a = 3 .
One can visit rather download a .ppt extension file from here for more info about CHINESE REMAINDER THEOREM .
Log in to reply
It is, as I said, a very simple algorithm. I would not consider that "easy," though.
All the same, nicely done. :D
Sorry,a typo: It should be 3 x − 1 .
p(x)=(x-1)Q1(x)+2 p(x)=(x-2)Q2(x)+5 p(x)=(x-1)(x-2)Q3(x)+ax+b
p(1)=2 p(1)=a+b p(2)=5 p(2)=2a+b
Hence, a+b=2 -a-b=-2 2a-a-b+b=-2+5 a=3, b=-1
2a+b=5 2a+b=5 a+b=2, 3+b=2, b=2-3=-1
Hence, the remainder will be ax+b=3x-1
Ans: 3x-1
by Division Algorithm,
Dividend=Divisor*quotient+remainder
So,p(x)=(x-1)*q(x)+2
putting x=1,
p(1)=0+2=2 -(i)
Also, p(x)=(x-2)*q'(x)+5
so, p(2)=5 -(ii)
Now, p(x)=(x-1)(x-2)*Q(x)+(ax+b)
putting x=1 and x=2
p(1)=a+b and p(2)=2a+b
so, a+b=2 and 2a+b=5 [from (i) and (ii)]
solving the two, we get a =3
We first consder the case in which ( x − 1 ) ( x − 2 ) = ( x − 1 ) or x = 3 . In this case, we have that 2 = 3 a + b . Now, let's consider the case in which ( x − 1 ) ( x − 2 ) = 2 ( x − 1 ) ⇒ x = 4 . Note that if n ≡ m ( m o d p ) , then n ≡ m ( m o d 2 p ) or n ≡ m + p ( m o d 2 p ) . We thus get that 2 = 4 a + b or 5 = 4 a + b . If we use the first equation, a solves to zero, and that's not the case, so we have to use the second equation. This gives us a = 3 .
Let p(x)=(x-1)(x-2)Q(x)+ax+b dividend=divisor multiplied by quotient plus remainder. Given p(1)=2=a+b and p(2)=5=2a+b by the remainder theorem. Solving, a=3
Let P(x) be
(x-1)(x-2).Q(x) + r(x) where r(x) is Ax + B
so, P(1) = A+B = 2
and, P(2)= 2A+B = 5
On solving we get, A= 3 and B=-1
Hence the answer is 3
f(x) = (x-1).g(x) + 2 ; f(1) = 2
f(x) = (x-2).h(x) + 5 ;f(2) = 5
f(x) = (x-1).(x-2).s(x) + ax + b
f(1) = a + b = 2 . ......(1)
f(2) = 2a + b = 5 ........(2)
then, by eliminating equation (1) and (2), we get that a is 3
Problem Loading...
Note Loading...
Set Loading...
P(x)=(x-1)q+2.........(1)
P(x)=(x-2)w+5.........(2)
P(x)=(x-1)(x-2)t+ax+b......(3). where q,w,t are quotients
Putting x=1 in 1 we get
P(1)=2,
Putting x=2 in 2
P(2)=5
Putting x=1 in 3
P(1)=a+b
Putting x=2 in 3
P(2)=2a+b...
Solving all this we get a=3